Solar facades for heating and cooling in buildings - Chan, Hoy-Yen (2011)
The aim of this thesis is to study the energy performance of a building integrated heating and cooling system. The research objectives are to investigate the system operating characters, to develop mathematical models for the heating and cooling systems, to demonstrate the technologies experimentally, to identify the best designs for a combined system and to investigate the cost effectiveness of the system. The main components of the systems are the aluminium plate façade and the building wall behind it, these form a plenum between them and the air is then heated or cooled as it flows through this plenum. Mathematical models were developed based on the energy balance equations and solved by matrix inversion method. These models were then validated with experimental results. The experiments were carried out in the laboratory with a facade area of 2m2. Two designs of facade were tested, i.e. flat and transpired plates. Results showed that the transpired design gave better thermal performance; the system efficiency for the flat plate was only about 30%, whereas it was about 85% for the transpired plate. On the other hand, a cooling system with double plenums was found to be better than a single plenum. Thus, a transpired plate with two plenums was identified as the best design for space heating and cooling. The cooling efficiency was nearly 2.0 even at low solar radiation intensity. A simulation study was carried out by assuming a 40m2 of façade was installed on an office building in London. The yearly energy saving was estimated as 10,877kWh, which is equivalent to 5,874kgCO2/year of emission avoidance. The system is calculated to cost about £70/m2, and for a discount rate of 5% and 30 years of lifetime, the payback period for this system would be less than a years.